Prevalence of Past and Reactivated Viral Infections and Efficacy of Cyclosporine A as Monotherapy or in Combination in Patients with Psoriatic Arthritis—Synergy Study: A Longitudinal Observational Study. (3rd April 2014) - Colombo, Delia; Chimenti, Sergio; Grossi, Paolo; Marchesoni, Antonio; Di Nuzzo, Sergio; Griseta, Vito; Gargiulo, Anna; Parodi, Aurora; Simoni, Lucia; Bellia, Gilberto
Abstract : We have prospectively evaluated psoriatic arthritis (PsA) patients for (1) seropositivity for former viral infections and seroconversion and (2) efficacy of cyclosporine A (CsA) alone or in combination with other immunosuppressants in a time period of 12 months. Screening included HBV antibodies and antigens, HCV antibodies and RNA, HSV 1-2, HZV, EBV, and CMV IgG, and IgM, HHV-6 DNA, and HIV 1-2 antibodies. PsA was evaluated by the Psoriasis Area Severity Index (PASI), the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and the Visual Analogue Scale (VAS). At baseline, 126 (56%) out of 225 evaluable patients had 2 or more seropositivities indicative of former infections, and 31 patients (13.8%) presented seropositivity for HCV, HBV, HSV-1 and -2, HHV-6, EBV, or parvovirus infection; one of them, positive for HBAg, was treated with lamivudine, while the remaining 30 received no specific treatment. None of the 31 patients developed virus reactivation. A reduction (P < 0.001 ) of PASI, BASDAI, and VAS scores was observed at 6 and 12 months. The treatment of PsA with CsA as monotherapy or in combination was safe and effective. In vitro experiments and clinical findings, including those from our study, suggest that CsA as monotherapy or in combination with biologics might be the treatment of choice in PsA HCV-positive patients.